Ultrasound Monitoring after Pelvis-Sparing Dismembered Pyeloplasty: High Sensitivity and Low Specificity for the Success of Operation - Kiblawi, Rim; Kuebler, Joachim F.; Petersen, Claus; Ure, Benno M.; Hofmann, Alejandro D. (European Journal of Pediatric Surgery, 2020)
Introduction A decrease in the anteroposterior diameter (APD) of the renal pelvis on ultrasound has been postulated to be indicative of sufficient pelvic drainage after pyeloplasty. Traditionally, pyeloplasty is combined with a reduction of the renal pelvis. We have recently demonstrated that resection of the pelvis during pyeloplasty is not necessary. We aimed to evaluate the efficacy of ultrasound APD measurements during follow-up to identify sufficient pelvic drainage in these patients.Materials and Methods Data from children (0–16 years) who underwent pelvis-sparing pyeloplasty in our institution from 2007 to 2018 were analyzed retrospectively. We included only those patients for whom pre- and postoperative ultrasound and renal scan data were available. Patients with a decrease versus patients with an increase in APD were analyzed with regard to urinary drainage and reoperation.Results Seventy-three patients who underwent follow-up at a mean of 3 months after operation were included; 61 showed a decrease in APD. Renal scan showed sufficient urinary drainage in 58 of them, with none requiring reoperation. Twelve patients had an increase in APD. Six of these showed free urinary drainage on renal scan; another six showed insufficient drainage, of whom five required reoperation. The positive predictive value of a decrease in APD was 1, and the negative predictive value of increase in APD was 0.42.Conclusion To our knowledge, this is the first study evaluating the efficacy of ultrasound measurements to identify patients with decompensated urinary drainage during early follow-up after pyeloplasty with pelvis sparing. Post- versus preoperative decrease in renal pelvis diameter appears to be sufficient to rule out recurrence of obstruction. Renal scan seems to be indicated only in cases with post- versus preoperative increase in the APD of the renal pelvis on ultrasound.
Keywords: pyeloplasty; hydronephrosis; anteroposterior diameter; ultrasound monitoring